Understanding unfolding and refolding of the antibody fragment (Fab) III: mapping covalent and non-covalent interactions during in-vitro refolding of light chain, heavy chain, and Fab. - Gani, Kayanat; Chirmade, Tejas; Ughade, Santosh; Thulasiram, Hirekodathakallu; Bhambure, Rahul (Biochemical Engineering Journal, 2022)
In-vitro refolding of the antibody fragments from inclusion bodies is a critical manufacturing bottleneck. We have previously reported that Fab refolding involves the formation of an intermediate. To further decode the refolding pathway, we have mapped the covalent and non-covalent interactions during in-vitro refolding of individual light chain (LC), heavy chain (HC), and intact Fab. Intrinsic fluorescence analysis was performed to map the non -covalent interactions, whereas time-dependent disulfide mapping was performed using LC-MS/MS analysis under non-reducing and reducing atmospheres. Refolding of purified LC, HC, and intact Fab (Biosimilar rHu Ranibi-zumab) was investigated in the study. Under the reducing condition, LC, HC, and intact Fab required around 96, 30, and 70 h, respectively, whereas, under non-reducing conditions, they required only 48, 10, and 48 h, respectively, to acquire the native conformation. The disulfide bond mapping revealed that the bond between LC_Cys23/Cys88 is more unstable. The peptides mapped with the inter-chain disulfide bond were identified at 48 h during the refolding and can be considered as the rate-limiting step in (Fab) refolding. We have also studied a new refolding strategy involving assembly of separately refolded LC and HC into Fab molecule. In this case the Fab refolding yield was low (18.0 +/- 1.36%), indicating inefficient assembly of refolded LC and HC chain into native Fab molecule.
Keywords: Antibody fragment; Disulfide bond formation; In-vitro refolding; Light and heavy chain; rHu Ranibizumab

Chromatography assisted in-vitro refolding and purification of recombinant peptibody: recombinant romiplostim a case study - Rana, Sunil; Ughade, Santosh; Kumthekar, Rupali; Bhambure, Rahul (International Journal of Biological Macromolecules, 2023)
In-vitro protein refolding is one of the key rate-limiting unit operations in manufacturing of fusion proteins such as peptibodies expressed using E. coli. Dilution-assisted refolding is the most commonly used industrial practice to achieve the soluble, native functional form of the recombinant protein from the inclusion bodies. This study is focused on developing a chromatography-assisted in-vitro refolding platform to produce the biologically active, native form of recombinant peptibody. Recombinant Romiplostim was selected as a model protein for the study. A plug flow tubular reactor was connected in series with capture step affinity chromatography to achieve simultaneous in-vitro refolding and capture step purification of recombinant Romiplostim. Effect of various critical process parameters like fold dilution, temperature, residence time, and Cysteine: DTT ratio was studied using a central composite based design of experiment strategy to achieve a maximum refolding yield of selected peptibody. Under optimum refolding conditions, the maximum refolding yield of 57.0 & PLUSMN; 1.5 % and a purity of over 79.73 & PLUSMN; 3.4 % were achieved at 25-fold dilution, 15 degrees C temperature, 6 h residence time with 6 mM and 10 mM of cysteine and DTT, respectively. The formation of native peptibody structure was examined using various orthogonal analytical tools to study the protein's primary, secondary, and tertiary structure. The amino acid sequence for the disulfide-linked peptide was mapped using collision-induced dissociation (CID) to confirm the formation of interchain disulfide bonds between Cys7-Cys7 and Cys10-Cys10 similarly for intra-chain disulfide bonds between Cys42-Cys102, and Cys148-Cys206. The developed protocol here is a valuable tool to identify high-yield scalable refolding conditions for multi-domain proteins involving inter-domain disulfide bonds.
Keywords: CE-SDS; Disulfide bonds; In-vitro refolding; Peptibody; Romiplostim

Mapping time dependent disulfide bond formation during in-vitro refolding of recombinant peptibody: a Fc-fusion protein - Kumthekar, Rupali; Rana, Sunil; Ughade, Santosh; Bhambure, Rahul (Biochemical Engineering Journal, 2023)
Disulfide bonds are commonly found in covalent interactions, which play a vital role in establishing the three-dimensional structure of proteins and maintaining their biological activity. This investigation is focused on time dependant mapping of intra and inter-disulfide bonds during in-vitro refolding of recombinant peptibody using LC-ESI-MS/MS. The selected recombinant peptibody is a homodimeric, aglycosylated Fc-fusion protein expressed in E. coli. The amino acid sequence in the disulfide bond containing peptides was confirmed at MS/MS level using the CID-based fragmentation approach. During in-vitro refolding of peptibody, a peptide with inter -chain disulfide bond is observed post 4 h, with low area intensity, and it reached a maximum in 96 h. How-ever, maximum area intensity was reached for the intra-chain disulfide bond in 72 h. Since cysteine residues responsible for intra-chain disulfide bonds are present in complex part of the Fc domain, formation of intra-chain disulfide bonds may be an overall rate-limiting step in recombinant Romiplostim refolding. Proper folding and contributions by non-covalent interactions will be required to form intra-chain disulfide bond. Monitoring time -based formation of such non-covalent interactions was carried out using intrinsic fluorescence during protein refolding. Observations from intrinsic fluorescence show that 4-6 h is most crucial time for domain formation. Observations from this study will help characterize structural integrity and quality during process and product development for consistent product quality.
Keywords: Disulfide bond formation; In -vitro refolding; Intrinsic fluorescence; Mass spectroscopy; Peptibody; Time based mapping

Mechanistic modeling of size exclusion chromatography-assisted in vitro refolding of the recombinant biosimilar teriparatide (PTH-34) - Ughade, Santosh; Rana, Sunil; Nadeem, Mohd; Kumthekar, Rupali; Mahajani, Sanjay; Bhambure, Rahul (ACS Omega, 2024)
In vitro protein refolding is one of the critical unit operations in manufacturing recombinant peptides expressed using Escherichia coli as host cells. This study is focused on designing size exclusion chromatography-assisted in vitro refolding process for biosimilar recombinant parathyroid hormone. Inclusion bodies (IBs) of recombinant parathyroid hormone were solubilized at higher pH, and in vitro refolding was performed using size exclusion chromatography. In the first part of the investigation, DoE-based empirical optimization was performed to achieve a higher refolding yield for a biosimilar recombinant parathyroid hormone. The effect of solubilized inclusion body (IB) feed volume, concentration of IBs, and residence time on in vitro refolding of recombinant teriparatide was studied using the Box-Behnken design. Size exclusion chromatography (SEC)-assisted in vitro refolding was performed at 8 C-degrees at pH 10.5 by using 20 mM Tris buffer. The maximum refolding yield of 98.12% was achieved at feed volume (12.5% of CV) and 20 mg/mL inclusion body (IB) concentration with a residence time of 50 min and a purity of 66.1% based on densitometric analysis using SDS-PAGE. In the latter part of the investigation, the general rate mechanistic model framework for size exclusion chromatography was developed and validated with the experimental results. The developed model helped in the accurate prediction of the elution volumes and product yield. The developed model also helps to predict the elution performance of a scalable column a priori. Post in vitro refolding, the formation of the native peptide structure was examined using various orthogonal analytical tools to study the protein's primary, secondary, and tertiary structures. The developed hybrid process development approach is a valuable tool toachieve high-yield, scalable refolding conditions for recombinant proteins without disulfide bonds.